Decision to Return Way Kambas National Park: The Role of Facilities, Tourist Attractions, and Price from the Perspective of Islamic Business Ethics - Anggraeni, Citra; Zulaikah, Zulaikah; Susanti, Yeni (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Tourism plays an important role in the Indonesian economy, including in Lampung Province which has natural resources such as beaches, lakes, dams, and nature reserves. One of the leading destinations is Way Kambas National Park (TNWK), which was closed due to the COVID-19 pandemic and is now open again with a focus on education and conservation. This study aims to examine the influence of facilities, tourist attractions, and prices on the decision to return to TNWK in the perspective of Islamic Business Ethics. The method used is quantitative with the help of SmartPLS 4, involving 97 respondents determined through the Lemeshow formula. The results of the analysis showed that the three variables facilities p-value of 0.006, tourist attractions p p-value of 0.021 and the price of p-value of 0.000 had a positive and significant effect on the decision to visit again because it is less than 0.05. Terms of the hypothesis test. Simultaneously, all variables also significantly affect the p-value of 0.000. Sustainable tourism in TNWK is based on Islamic Business Ethics, which integrates the principles of Justice, amanah, maslahah, and non-destructive. This unique approach contributes significantly by demonstrating that tourism based on Islamic values can be a holistic solution to achieve economic, social, and environmental sustainability.